ALIH KODE DAN CAMPUR KODE DALAM FILM PENDEK PRASAJA KARYA PANIRADYA KAISTIMEWAN: KAJIAN SOSIOLINGUISTIK - Auliyani, Zalfa; Deswijaya, R. Adi; Efendi, Agus; Widiatmi, Tri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The phenomenon of using more than one language often occurs in bilingual and multilingual communities, particularly in everyday interactions. This phenomenon is also appear in the dialogues of the characters in the short film Prasaja, which demonstrates the use of more than one language in the communication process. Therefore, this study aims to describe the forms of code-switching and code-mixing in Paniradya’s short film Prasaja, as well as the factors influencing the occurrence of these phenomena. The research method employed is qualitative descriptive. The data source for this study is the short film Prasaja by Paniradya Kaistimewan, released in 2022. The research data consists of the dialogues of the characters in the short film Prasaja by Paniradya Kaistimewan. Data collection was conducted using observation and note-taking techniques. Data analysis involved data collection, data reduction, data presentation, and drawing conclusions. The results of the study indicate that in the dialogues of the film Prasaja, instances of code-switching were found, specifically inward code-switching. In addition, several forms of code-mixing were also found, including inward code-mixing, outward code-mixing, and mixed code-mixing. Factors contributing to code-switching and code-mixing include the speaker, the interlocutor, role identification, variety identification, and the desire to explain or interpret.